1991
DOI: 10.1172/jci115378
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine stimulation by erythropoietin and autonomous growth of human erythroid leukemic cells in vitro.

Abstract: Autonomous colony formation is a frequent event in erythroleukemia. In 13 cases of early erythroid leukemias, we investigated whether erythropoietin (Epo) autocrine stimulation was responsible for the growth factor autonomy. Epo transcripts were detected by Northern blotting in cells from one patient. These cells also expressed an Epo receptor (1,000 receptors per cell) with a 420-pM affinity and Epo was detected in the supernatant of cultured cells. In 8 of the 13 cases, Epo transcripts were revealed by the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 62 publications
1
28
0
1
Order By: Relevance
“…We could first try to see up to which extent we could use the same model with different parameters values for modelling the appearance of erythroleukemia. It has for example been shown that an autocrine EPO production occurred in human erythroleukemia (Mitjavila et al, 1991). In our model this can be modelled quite simply by modifying the value of β.…”
Section: Discussionmentioning
confidence: 99%
“…We could first try to see up to which extent we could use the same model with different parameters values for modelling the appearance of erythroleukemia. It has for example been shown that an autocrine EPO production occurred in human erythroleukemia (Mitjavila et al, 1991). In our model this can be modelled quite simply by modifying the value of β.…”
Section: Discussionmentioning
confidence: 99%
“…The mutation in VHL gene in these cells may affect their further development or differentiation into mature cells. The retention of Epo and EpoR coexpression in these precursor cells may lead to cell proliferation via the autocrine stimulation 27 and become a critical pathogenetic step in tumor formation. Our results indicate that sporadic and VHL-associated CCRCCs not only share genetic and morphological features but also share the autocrine loop pathway of Epo/EpoR coexpression.…”
Section: Discussionmentioning
confidence: 99%
“…It is fascinating to speculate that constitutively activated signal transduction pathway constitutively, can be a critical step in leukemogenesis. [34][35][36][37][38][39] We should also bear in mind that MAPKs may specifically phosphorylate and transactivate the transcription factors and that they may then regulate the tyrosine kinase, including receptor tyrosine kinases, might be…”
mentioning
confidence: 99%